Toward a Microencapsulated 3D hiPSC-Derived in vitro Cardiac Microtissue for Recapitulation of Human Heart Microenvironment Features - Abecasis, Bernardo (2021)
SAICTPAC/0047/2015 PTDC/BTMSAL/32566/ 2017 PTDC/MEC-CAR/29590/2017 UIDB/04462/2020 UIDP/04462/2020 H2020, ID:874827 SFRH/BD/52475/2013 SFRH/BPD/120595/2016